Effects of temperature, deposition time and catalyst loading on the synthesis of carbon nanotubes in a vertical CVD reactor - Hanaei, Hengameh (2011)
Carbon nanotubes (CNTs), were discovered by Ijima in 1991. They have special electrical, mechanical and electronic properties that make them attractive for a lot of applications. However, there is no clear relation between synthesis parameters and CNTs growth. Therefore more data investigations are required for Vertical CVD synthesis of CNTs. This research intend to investigate the effects of some synthesis parameters, namely, reaction temperature, catalyst loading, deposition time on Vertical CVD growth of CNTs. In present study, CNTs were produced through decomposition of acetone over a prepared catalyst Iron and Molybdenum supported on Alumina (Fe-Mo/AL2O3). The effects of those parameters on Vertical CVD synthesis of CNTs were studied using analysis of variance (ANOVA). After each run the product, including deposited carbon and catalyst, was characterized using different analysis techniques. The morphology of as grown CNTs was observed by Scanning Electron Microscope (SEM). Thermo Gravimetric Analysis (TGA) was applied as this technique can reveal different forms of the carbon deposits (eg. amorphous and CNTs) according to their different thermal stabilities. Besides that, the effects of parameters on carbon deposit yield as well as their interactions were statistically studied using ANOVA. Finally, the appropriate values for parameters under study towards effective Vertical CVD synthesis of CNTs were determined full factorial design of experiments method. This research demonstrated that by increasing the reaction temperature to 950°C, more amorphous carbon was observed due to deactivation of catalyst at high temperature. It was also observed that by increasing the duration time, the yield of CNTs had decreased and by decreasing the catalyst loading the yield and quality of CNTs had increased. It was proved that there is a significant interaction between parameters under observation. In other words, synthesis parameters are not independent variable. As a result of that the quality and yield of the CNTs were appropriate achieved at 750°C reaction temperature, 40 min deposition time and 5 gr catalysts loading.